2015
DOI: 10.31186/jspi.id.10.1.13-21
|View full text |Cite
|
Sign up to set email alerts
|

Respon Fisiologis Sapi Perah Dara Fries Holland yang Diberi Konsentrat dengan Tingkat Energi Berbeda

Abstract: The objective of the research was to study effects of feed energy of concentrate relationship with environment on physiological response of dairy heifers. The study used four dairy heifers with four treatments of concentrate energy in latin square design 4x4. The treatments of total digestible energy (TDN) were : P1 (TDN 60%), P2 (TDN 65%), P3 (TDN 70%), and P4 (TDN 75%) with crude protein (CP) 12-15%. The research was carried out for 4 periods consisting of 21 days each period. Variables observed were environ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
4

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 1 publication
(1 reference statement)
1
2
0
4
Order By: Relevance
“…Environmental physiology influences the sustainability of dairy cattle business. According to Suherman & Purwanto (2015) the factors of temperature, humidity, solar radiation, and wind speed affect the physiological conditions of dairy cattle. During dry season, forage feed and water will be decreasing, resulting in minimal intake of forage and drinking water for dairy cows.…”
Section: Risk Evaluationmentioning
confidence: 99%
“…Environmental physiology influences the sustainability of dairy cattle business. According to Suherman & Purwanto (2015) the factors of temperature, humidity, solar radiation, and wind speed affect the physiological conditions of dairy cattle. During dry season, forage feed and water will be decreasing, resulting in minimal intake of forage and drinking water for dairy cows.…”
Section: Risk Evaluationmentioning
confidence: 99%
“…Dairy cows will generally stand up if the animals are fed and when will be milked. Suherman and Purwanto (2015) reported that at high temperatures dairy cows will show standing behavior with a relatively shorter time and lie down with a relatively long time. Yani et al (2007) state that the temperature range in subtropics regions which is good for Friesian Holstein is 5 to 25 °C so that Friesian-Holstein cattle are very sensitive to changes in microclimate especially temperature and humidity.…”
Section: Cows Behavior and Environmental Datamentioning
confidence: 99%
“…Hal tersebut berkaitan dengan aktivitas metabolisme, dimana produksi panas yang tinggi mengakibatkan aktivitas metabolisme yang lebih cepat dibandingkan kambing dengan produksi panas yang rendah. Suherman & Purwanto (2015) bahwa pakan yang dikonsumsi ternak bisa berpengaruh meningkatkan laju produksi panas dalam tubuh atau disebut juga dengan efek kalorigenik pakan dan untuk mempertahankan kondisi homeostasis. Menurut Yani & Purwanto (2006), peningkatan denyut jantung dan pernafasan akan mempercepat aliran panas tubuh ke permukaan tubuh yang selanjutnya dikeluarkan ke lingkungan melalui konduksi, konveksi, radiasi maupun evaporasi, sehingga suhu tubuh relatif konstan.…”
Section: Respon Fisiologis (Denyut Jantung Frekuensi Respirasi Dan unclassified